A fluorescent approach for identifying P2X1 ligands. (November 2015) - Ruepp, Marc-David; Brozik, James A.; de Esch, Iwan J.P.; Farndale, Richard W.; Murrell-Lagnado, Ruth D.; Thompson, Andrew J.
Abstract: There are no commercially available, small, receptor-specific P2X1 ligands. There are several synthetic derivatives of the natural agonist ATP and some structurally-complex antagonists including compounds such as PPADS, NTP-ATP, suramin and its derivatives (e.g. NF279, NF449). NF449 is the most potent and selective ligand, but potencies of many others are not particularly high and they can also act at other P2X, P2Y and non-purinergic receptors. While there is clearly scope for further work on P2X1 receptor pharmacology, screening can be difficult owing to rapid receptor desensitisation. To reduce desensitisation substitutions can be made within the N-terminus of the P2X1 receptor, but these could also affect ligand properties. An alternative is the use of fluorescent voltage-sensitive dyes that respond to membrane potential changes resulting from channel opening. Here we utilised this approach in conjunction with fragment-based drug-discovery. Using a single concentration (300 μM) we identified 46 novel leads from a library of 1443 fragments (hit rate = 3.2%). These hits were independently validated by measuring concentration-dependence with the same voltage-sensitive dye, and by visualising the competition of hits with an Alexa-647-ATP fluorophore using confocal microscopy; confocal yielded k on (1.142 × 10 6 M −1 s −1 ) and k off (0.136 s −1 ) for Alexa-647-ATP ( K d = 119 nM). The identified hit fragments had promising structural diversity. In summary, the measurement of functional responses using voltage-sensitive dyes was flexible and cost-effective because labelled competitors were not needed, effects were independent of a specific binding site, and both agonist and antagonist actions were probed in a single assay. The method is widely applicable and could be applied to all P2X family members, as well as other voltage-gated and ligand-gated ion channels. This article is part of the Special Issue entitled 'Fluorescent Tools in Neuropharmacology'. Highlights: A novel fluorescence-based screening approach for identifying P2X1 receptor ligand candidates. Fragment-based drug discovery applied to ligand-gated ion channels. The use of confocal microscopy to determine the kinetics and affinity of Alexa-647-ATP binding to P2X1 receptors. Alexa-647-ATP for imaging P2X1 receptors on live cells.